2017
DOI: 10.1136/rmdopen-2017-000446
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of polyarteritis nodosa with tocilizumab: a new therapeutic approach?

Abstract: We describe the effect of interleukin 6 (IL-6) blockade using tocilizumab (TCZ) for inducing and maintaining remission of refractory polyarteritis nodosa (PAN). Three patients with refractory PAN defined according to the American College of Rheumatology criteria were treated with TCZ infusions (8 mg/kg) on a monthly basis. All of them had severe cutaneous and articular involvement with elevated biological inflammatory markers. One suffered from a neuritis multiplex and one from renal and digestive damage. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ]. A report showed that epidural administration of TCZ reduced pain due to sciatica with lumbar spinal stenosis [ 188 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ]. A report showed that epidural administration of TCZ reduced pain due to sciatica with lumbar spinal stenosis [ 188 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…Indeed, treatment of skin necrosis with in iximab appeared effective in our study. Although not used in the current study, the interleukin-6 blocker tocilizumab has also shown promise for the treatment of vasculitis [31,32]. Strategies that aim to reduce the treatment burden as much as possible should be a major goal for physicians when attempting to achieve remission.…”
Section: Discussionmentioning
confidence: 97%
“…Infliximab appeared to be effective in treating skin necrosis in our study. Although not used in the current study, the interleukin-6 blocker tocilizumab has also shown promise for the treatment of vasculitis 29 , 30 . Strategies that aim to reduce the treatment burden as much as possible should be a major goal for physicians when attempting to achieve remission.…”
Section: Discussionmentioning
confidence: 99%